Applications of atomic data to studies of the Sun - Young, Peter R. (The European physical journal. D, Atomic, molecular, and optical physics, 2024)
The Sun is a standard reference object for astrophysics and also a fascinating subject of study in its own right. X-ray and extreme ultraviolet movies of the Sun’s atmosphere show an extraordinary diversity of plasma phenomena, from barely visible bursts and jets to coronal mass ejections that impact a large portion of the solar surface. The processes that produce these phenomena, heat the corona and power the solar wind remain actively studied and accurate atomic data are essential for interpreting observations and making model predictions. For the Sun’s interior intense effort is focused on resolving the “solar problem,” (a discrepancy between solar interior models and helioseismology measurements) and atomic data are central to both element abundance measurements and interior physics such as opacity and nuclear reaction rates. In this article, topics within solar interior and solar atmosphere physics are discussed and the role of atomic data described. Areas of active research are highlighted and specific atomic data needs are identified. Graphical abstract An image of a solar active region obtained with the 193 A channel of SDO/AIA, showing plasma at around 1.5 million degrees.